Dampak Implementasi Tata Kelola Teknologi Informasi (IT Governanace) Terhadap Return on Asset (ROA) - Indra Yudha Mailana; Linda Ayu Oktoriza; Maria Safitri; Vicky Oktavia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Given technological developments and globalization, effective IT governance has become crucial in supporting corporate objectives. This study analyzes the impact of IT governance implementation on financial performance, as measured by Return on Assets (ROA), in industrial companies listed on the Indonesia Stock Exchange. This study examines the relationship between the elements of IT governance, namely Board IT Governance Processes (BITGP), Board IT Governance Structure (BITGS), and Board IT Governance Relational (BITGR) with Return on Assets (ROA). The results show that these three elements have a positive and significant effect on Return on Assets (ROA), indicating that good IT governance can improve operational performance and create added value for companies. These results support agency theory and emphasize the importance of effective communication between management and stakeholders. This study recommends that companies strengthen their IT governance structures and processes in order to adapt to the digital era and innovate, thereby improving their competitiveness and long-term financial.